Mechanical Properties of Kenaf Reinforced Polypropylene Composites Added with Oil Palm Shell Powder and Its Activated Carbon - Abd Latif, Mohd Abrar; Abd Manaf, Mohd Edeerozey; Shamsudin, Zurina (Universiti Teknikal Malaysia Melaka, 2017)
The application of natural fibers in composite is very encouraging because of its many benefits such as more environmental friendly and cost reduction. The mechanical properties of kenaf fiber reinforced polypropylene composite added with two different types of bio-based fillers, namely oil palm shell powder (OPSP) and activated carbon of oil palm shell powder (ACOPSP) are studied. The composites were prepared by melt mixing of the materials using internal mixer, followed by extrusion and compression molding processes. The samples were prepared at 4 different weight percentage of filler content, i.e., 0, 5, 10 and 15 phc.